PROGRAM JUMAT LITERASI SEBAGAI UPAYA MENINGKATKAN MINAT BACA SISWA DI SMAN 3 KARAWANG - Maulana Tahsin, Alwan; Permana, Hinggil; Az Zahro, Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students' interest in reading stays low, which is a big problem in education because it can lower the quality of learning and the results students achieve. To tackle this problem, SMAN 3 Karawang started the Friday Literacy Program as a way to build a stronger reading culture and boost students' interest in reading. This study was done to explain how the Friday Literacy Program was carried out, find out what helped and what slowed down its implementation, and look at how much it helped improve students' interest in reading at SMAN 3 Karawang. This study used a qualitative method and followed a descriptive approach. The study included the school principal, teachers, and students, who were chosen using purposive sampling. Data was gathered by watching, talking to people, and keeping records. The data analysis was done using the Miles and Huberman interactive model, which involves steps like reducing the data, presenting it in a clear way, and then making final conclusions based on it. The data's accuracy was checked by using different sources and different methods. The study showed that the Friday Literacy Program was carried out in a planned and organized way.It involved reading activities done before regular classes, backed by school rules, with teachers actively taking part and having access to reading materials. The program helped students develop a stronger interest in reading, shown by better reading habits, more excitement about joining literacy events, and improved understanding of what they read. The program still faced some difficulties, like students not being very motivated, not having enough interesting books to read, and not managing their time very well. So, keeping the Friday Literacy Program moving forward with new ideas and having everyone like schools, teachers, students, and parents work together really well is important to keep and improve the school's focus on reading and learning.